Perceptions of the importance of cost systems within peruvian companies (Costos y Gestión, 2025)
This study explores managers perceptions of the importance of cost systems in operational and strategic decision-making, as well as the factors influencing these perceptions. Using a relational scope and a quantitative approach, the research is based on a survey of managers responsible for cost systems in Peruvian companies. Factor analysis was employed to identify key perception components, while the Mann-Whitney U and Kruskal-Wallis tests were used to assess the effects of ERP usage and business sector differences. According to the results, standard costing and full costing are the most widely used systems, primarily for financial reporting, profitability analysis, and budgeting, particularly in short-term decision-making. ERP implementation and the business sector moderately influence managerial perceptions. These results provide a basis for future confirmatory studies on the relevance and determinants of cost system adoption. The study underscores the need for enhanced training in analytical tools for cost system managers to improve decision-making at both operational and strategic levels.
Keywords: cost accounting; management control; ERP; costing systems